Critical Issues in the Science of Reading: Striving for a Wide-Angle View in Research. (November 2021) - Hoffman, James V.; Cabell, Sonia Q.; Barrueco, Sandra; Hollins, Etta R.; Pearson, P. David
This report reflects a panel presentation and discussion at the 2020 Literacy Research Conference focused on the science of reading (SoR). Each panelist presents a summary of the presentation and incorporates the comments of the Literacy Research Association (LRA) members attending the session virtually and posting in the chat room. Each presentation takes a critical stance on the possibilities for expanding the lens for the SoR. Concerns are raised regarding the narrow interpretation of the SoR and impact of this narrow conception on research, theory, and practice.